Desenvolvimento de liofilizador para conservação de alimentos - Balcewicz Junior, Leonardo (2020)
The purpose of this paper was to develop equipment for dehydrating food in order to add value, providing alternatives for conservation and commercialization between harvests. The lyophilizer, in prototype format, was developed with local labor, carbon steel structure, dehydration compartments in AISI 304 stainless steel and performance equipment found in the national market. We understand that this product is a viable alternative to food production from rural properties, because it can conserve agricultural products for periods of six months to one year to be marketed between harvest periods. The time variation stems from the fact that each product has different conditions and characteristics. The results observed with the tests performed in relation to the different foods tested showed the functioning and efficiency of the equipment developed.